Impact of processing methods on microbial load of reared and wild-caught edible crickets (Scapsipedus icipe and Gryllus bimaculatus) in Kenya - Gatheru, J.W.; Khamis, F.M.; Ombura, F.L.O.; Nonoh, J.; Tanga, C.M.; Maina, J.; Mohamed, S.A.; Subramanian, S.; Ekesi, S.; Fiaboe, K.K.M. (Brill, 2019)
The microbial composition of farmed and wild Scapsipedus icipe and Gryllus bimaculatus is presented. The aim of this study is to determine the microbial load of the two cricket species and evaluate the efficiency of processing methods (boiling, sun-drying, freeze-drying, snap-freezing and deep-frying) in reducing microbial counts. Farmed and wild species were compared based on microbial diversity. Fresh crickets had high microbial counts, bacterial and fungal populations ranged from 4.26-4.58 log cfu/g and 3.48-4.48 log cfu/g fresh weight, respectively. Upon processing, microbial counts reduced, bacterial counts ranged from 1.00-2.08 log cfu/g dry weight (boiled) and 2.70-3.34 log cfu/g dry weight (sun-dried). Fungal counts ranged from1.85-1.95 log cfu/g dry weight (boiled) and 2.95-3.51 log cfu/g dry weight (sun-dried). Deep-frying, freeze-drying and snap-freezing emerged as the best processing methods. Although there is no alarm in consuming fresh crickets, a processing method is advisable to minimize any possible risks.